UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPAS, MATERI “INDONESIAKU KAYA HAYATINYA” MENGGUNAKAN MODEL INQUIRY TERBIMBING, BERBANTUAN MEDIA MONOPOLI DI SDN BENDO 2 - Aprinindya Putri Mulia; Agista Faraditya Megananda; Levia Tivani Yahya; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research conducted aims to determine the improvement and achievement offifth grade students' learning in the subject of science through the inquiry learningmethod and also the effectiveness of the inquiry learning method assisted bymonopoly media in improving learning achievement. This type of research isclassroom action research (CAR). Fifth grade students of SDN Bendo 02 totaling 14students, consisting of 8 male students and 6 female students became the subjectsof this research. The data collection technique used was a test and non-test in theform of observation. The research procedure in this study consisted of pre-cycle,cycle I and cycle II. The results showed that there was an increase in learningachievement where in the pre-cycle the percentage of acceptance was 28%, thencycle I the percentage of completion was 28% and in cycle II the percentage ofcompletion was 100%. So the learning achievement of fifth grade students of SDNBendo 02 on the material "Indonesiaku Kaya Hayatinya" in the subject of scienceassisted by monopoly media using the inquiry learning method can be said to besuccessful or complete.